Immunohistochemical demonstration of CD23 expression on lymphocytes in rheumatoid synovitis. Issue 4 (April 1991) - Hellen, E A; Rowlands, D C; Hansel, T T; Kitas, G D; Crocker, J
Abstract : The leucocyte antigen CD23 is expressed by B lymphocytes following activation by a number of stimuli and functions as an IgE receptor, and in its soluble form, as a putative B cell growth factor. The expression of CD23 on the surface of lymphocytes in paraffin wax sections of synovial biopsy specimens was studied using a novel mouse monoclonal antibody, BU38. Specimens were investigated from nine cases of rheumatoid arthritis, six cases of osteoarthritis, and eight cases of chronic inflammation in articular and non-articular tissues. CD23 was expressed on a high proportion of lymphocytes in all forms of chronic inflammation and was not specific for rheumatoid arthritis. It may be a characteristic feature of any chronic inflammatory response. As CD23 was found on the surface of lymphocytes in many cases of these arthritides, sCD23 in serum or synovial fluid may yet prove a useful marker for the severity of the inflammatory infiltrate.